2021
DOI: 10.3389/fpubh.2021.685141
|View full text |Cite
|
Sign up to set email alerts
|

Baidu Index and COVID-19 Epidemic Forecast: Evidence From China

Abstract: With the global spread of the Coronavirus epidemic, search engine data can be a practical tool for decision-makers to understand the epidemic's trends. This article uses trend analysis data from the Baidu search engine, the most widely used in China, to analyze the public's attention to the epidemic and the demand for N95 masks and other anti-epidemic materials and information. This kind of analysis has become an important part of information epidemiology. We have analyzed the use of the keywords “Coronavirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 18 publications
2
40
0
Order By: Relevance
“…Relying on traditional laboratory and clinical data to publish weekly statistics for countries and regions usually results in a lag of 1-2 weeks (27). But our data showed that the popularly used Internet search engines, Baidu, and the social media platform, Sina Weibo, were able to predict the disease outbreak 6-19 days earlier than the traditional surveillance systems.…”
Section: Interpretations and Policy Recommendationsmentioning
confidence: 71%
See 2 more Smart Citations
“…Relying on traditional laboratory and clinical data to publish weekly statistics for countries and regions usually results in a lag of 1-2 weeks (27). But our data showed that the popularly used Internet search engines, Baidu, and the social media platform, Sina Weibo, were able to predict the disease outbreak 6-19 days earlier than the traditional surveillance systems.…”
Section: Interpretations and Policy Recommendationsmentioning
confidence: 71%
“…But our data showed that the popularly used Internet search engines, Baidu, and the social media platform, Sina Weibo, were able to predict the disease outbreak 6-19 days earlier than the traditional surveillance systems. Big data monitoring of the epidemic can track the trends of infectious diseases and epidemics faster than traditional monitoring systems (27), which could buy time for controlling outbreaks of these diseases and reducing the risk of transmission to humans (37). This finding suggests that the government could build a tool for infectious disease surveillance based on BDI and SMI, which should be considered as supplementary to the traditional public health monitoring systems.…”
Section: Interpretations and Policy Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the novel coronavirus was used as the keyword, and the time span was from January 9, 2020 (when the pathogen was preliminarily determined to be COVID-19), to April 14, 2020 (when the ICU ward of Wuhan Jinyintan Hospital announced that they had ’zero COVID-19 patients’; a monumental victory in the control of COVID-19) [ 35 , 36 ]. Based on the Baidu index, the spatial and temporal differences of and factors that influence the novel coronavirus attention network were analysed, and the spreading trend and severity of the epidemic in various provinces in China were determined to scientifically and accurately assess the form of the national epidemic and provide a basis for promoting the precise prevention and control of the epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…Mertens ( 6 ) utilizes 20 years of German manufacturing microdata to explore the reasons for the global decline in labor's share of economic output, arguing that the firms' market power in labor and products explains half of the decline in labor shares. Elsayed et al ( 7 9 ) discussed economic uncertainty, COVID-19, and labor market regulations. Chen et al ( 10 13 ) also examined the effects of conflict, social mobility and stringency measures on COVID-19 and the economy.…”
Section: Literature Reviewmentioning
confidence: 99%